(3eONd JMdjdj ddeaGgje h GdYdGbGJ ,GdGSJQGJjLjGJ h GdYedjGJ , GdefGgL h GdJbfjGJs - (3WGgQ eMSf(B, (3GdZGdHjs; (3GMeO Ydj UGdM(B, s ((3YeGf(B:s (3OGQ hGFd(B,s, 2009)
(3GdGWGQ GdeaGgjej ddJWhQ GdJfXjej h efWdbGJg GdGSGSjI , YdGbI GdJWhjQ GdJfXjej HGdJMhd GdJfXjej h bjeg h CNdGbjGJg h HYGde GdGOGQI h GdbjGOI GdJMhjdjI h fJGFLgG , GOGQI GdJWhjQ GdJfXjej h GSJQGJjLjGJg h cPdc YedjGJ gPG GdJWhjQ h Jbhje HQGeLg , eaghe efGgL GdJWhjQ GdJfXjej h eLGdGJgG h CfhGYgG h CNjQG eaghe JbfjGJ GdJWhjQ GdJfXjej h CSS JUfjagG h GSJNOGeGJgG (B.s
(3eQGLY (B: (3dcd aUd eQLYs
Keywords: (3GdGOGQIs; (3GdJNWjWs; (3GdJfXjes